Effect of lithium triflate (LiTf) salt on the structural and electrochemical properties of the pectin-based solid polymer electrolytes films / Nur Jannah Abdul Halim ... [et al.] - Abdul Halim, Nur Jannah; Muhd Zailani, Nabilah Akemal; Nazir, Khuzaimah; Syed Ismail, Sharifah Nafisah; Abdul Latif, Famiza (Research Management Institute (RMI), 2024)
Currently, liquid electrolytes (LEs) that have been used in many electrochemical devices, face safety concerns due to leakage problems. Consequently, solid polymer electrolytes (SPE) consisting of a natural polymer host that is leak-proof, biodegradable, and flexible are widely studied. In the current study, the effect of various weight percentages (%) (i.e.: 10, 20, 30, 40, and 50 wt.%) of lithium triflate (LiTf) salt on the structural and electrochemical properties of pectin-based SPE films was investigated. The SPE films were prepared using the solvent casting technique. Solid, flexible, and self-supporting films of pectin-based SPE were successfully acquired by the addition of up to 50 wt.% of LiTf. As proven by FTIR analyses, there occur interactions between the lithium cation and the pectin coordinating sites (OH and C=O). These interactions minimized the formation of hydrogen bonding between pectin chains, hence explaining the formation of flexible films. Also, the polymer-salt interactions contributed to the improvement in the amorphous phase of the system. The minimized formation of hydrogen bonding, improvement in the amorphous phase, and the increased amount of charge carriers in the LiTf-doped pectin-based SPE had contributed to the increase in the ionic conductivity of the system with salt content.